Factors Impacting Adoption of Organic Farming in Chitwan District of Nepal - Singh, Mrinila; Maharjan , Keshav Lall; Maskey, Bijan (Asian Journal of Agriculture and Rural Development, 2015)
Organic farming provides social, economic and environmental benefits but it still occupies a small share of the overall agriculture sector. The objective of this study is to assess factors identifying the underlying issues leading farmers to adopt organic farming. The study was conducted in Chitwan district where indiscriminate use of agro-chemicals is very much existent but the concept of organic farming is also emerging especially in three village development committees within the district; namely Phoolbari, Shivanagar and Mangalpur. Based on field observation, the farming system is categorized into organic, partial organic and inorganic farming. Data from 285 purposively selected households were analyzed using Multinomial Logit model in Stata 13. Results show that older farmers are reluctant to change and thus has lower tendency to adopt organic farming. On the other hand, livestock holding is very crucial as it supplies the much needed manure for fertilizing the soil. More significantly membership in a group formed for the purpose of organic farming and the extent of activities such as training conducted through it has been very much successful in encouraging farmers to convert to organic or at least partial organic farming. Thus, formation of such groups in other areas could be the most effective tool for large scale conversion to organic farming.